State of Rhode-Island and Providence Plantations : At a meeting of the committee appointed to act during the recess of the General-Assembly, held at the Court House in Newport, on the twelfth day of September, A.D. 1776. Resolved that, to raise the battalion of militia now ordered . (LLMC-digital (Series), 1776)
Resolve on methods of raising the number of men required, equipment to be furnished, wages allowed, and the proportion of commissioned officers in each county.